Early childhood language learning from a neurolinguistic perspective: A systematic review of brain development in language - Sulastri; Syarifah Mulyana; Heru Kurniawan (Universitas Islam Negeri Raden Intan Lampung, 2026)
Background: Early childhood language development is closely linked to the maturation and plasticity of the brain’s language system. Despite this, early childhood education programs often overlook neurolinguistic evidence that underlies language acquisition. Objective: This study aims to systematically review neurolinguistic research on early childhood brain language development and explore its implications for language learning practices. Methods: A systematic review was conducted following the PRISMA guidelines. Articles were retrieved from Scopus, Web of Science, and Google Scholar databases. Inclusion criteria comprised peer-reviewed studies published between 2021 and 2026 that focused on neurolinguistics, early childhood language development, or language learning. A total of 15 eligible articles were selected and analyzed using thematic analysis. Results: The review revealed that interactive language stimulation, multimodal learning approaches, and emotionally supportive environments strengthen neural connectivity between language-related brain regions, particularly those associated with language comprehension and production. Neuroimaging studies further indicated that rich linguistic input contributes to more efficient activation of neural networks involved in early language acquisition. Conclusion: The findings highlight the importance of aligning early childhood language learning with brain developmental mechanisms. Integrating evidence-based neurolinguistic principles into educational practice may enhance language acquisition and support optimal language development in young children.